The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/ctra-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

The Creative Self-Concept as a Mediator Between Openness to Experience and Creative Behaviour

Abstract: This study examined the mediation effect of creative self-concept on the relationship between Openness to Experience and creative behaviours among university students. Participants in the study completed self-report measures of Openness to Experience, creative behaviours and creative self-concept. Structural equation modelling revealed that, as predicted, Openness to Experience was indirectly related to creative behaviours through creative self-concept. Implications for future research and limitations of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
(34 reference statements)
3
12
0
Order By: Relevance
“…Importantly, there are reasons to believe that tCSE not only predicts such varying creativity-related outcomes as creative activity or creative achievement, but also that it mediates the relationship between different characteristics. This mediational hypothesis was recently proposed (Karwowski & Barbot, 2016; and empirically demonstrated in a growing number of studies (Chen, 2016;. According to this perspective, several characteristics usually described under the umbrella of potential-be it creative ability, personality, or intelligence-build creative confidence thanks to the effectiveness of functioning and previous successes.…”
Section: Critical Thinking Disposition and Cscmentioning
confidence: 93%
See 2 more Smart Citations
“…Importantly, there are reasons to believe that tCSE not only predicts such varying creativity-related outcomes as creative activity or creative achievement, but also that it mediates the relationship between different characteristics. This mediational hypothesis was recently proposed (Karwowski & Barbot, 2016; and empirically demonstrated in a growing number of studies (Chen, 2016;. According to this perspective, several characteristics usually described under the umbrella of potential-be it creative ability, personality, or intelligence-build creative confidence thanks to the effectiveness of functioning and previous successes.…”
Section: Critical Thinking Disposition and Cscmentioning
confidence: 93%
“…Karwowski and Lebuda () have demonstrated that tCSE partially mediates the relationship between openness and creative activity. Chen () showed full mediation of creative self‐concept in the relationship between openness and creative behavior. In a more elaborate “creativity behavior as an agentic action” (CBAA) model, Karwowski and Beghetto (in press) proposed that while creative confidence builds a sense of agency and thus mediates the relationship between creative potential and creative achievement, valuing creativity moderates this link.…”
Section: Csc and Scientific Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a person's belief system participates in the agentic action of transition from creative potential to creative behavior . People often choose not to try creative behaviors when they are unsure of their abilities (i.e., they hold low creative confidence, Chen, 2016;Choi, 2004), or when the perceived personal value of creativity is low (Plucker & Makel, 2010), or see SELF-REGULATION AND CREATIVITY people in the creative process. In sum, the support-and-sustain component of self-regulation rests on planning and implementation, persistence in the face of obstacles, and managing emotions.…”
Section: Stephen King On Writingmentioning
confidence: 99%
“…This belief is highly malleable and influenced by sociocognitive and environmental factors (Bandura, 1997). Creative confidence mediates the relationships between creative potential and creative behavior (Beghetto et al, 2020;Chen, 2016;Choi, 2004). People who believe in their creative abilities are more engaged in creative tasks and challenges (Carmeli & Schaubroeck, 2007;Pretz & McCollum, 2014;Tierney & Farmer, 2002;Tierney & Farmer, 2011).…”
Section: Parents' Creative Self-beliefsmentioning
confidence: 99%